Dryas as a Model for Studying the Root Symbioses of the Rosaceae - Billault-Penneteau, Benjamin; Sandré, Aline; Folgmann, Jessica; Parniske, Martin; Pawlowski, Katharina (Frontiers in Plant Science, 2019)
The nitrogen-fixing root nodule symbiosis is restricted to four plant orders: Fabales (legumes), Fagales, Cucurbitales and Rosales (Elaeagnaceae, Rhamnaceae and Rosaceae). Interestingly all of the Rosaceae genera confirmed to contain nodulating species (i.e. Cercocarpus, Chamaebatia, Dryas and Purshia) belong to a single subfamily, the Dryadoideae. The Dryas genus is particulary interesting from an evolutionary perspective because it contains closely related nodulating (Dryas drummondii) and non-nodulating species (Dryas octopetala). The close phylogenetic relationship between these two species makes Dryas an ideal model genus to study the genetic basis of nodulation by whole genome comparison and classical genetics. Therefore, we established methods for plant cultivation, transformation and DNA extraction for these species. We optimized seed surface sterilization and germination methods and tested growth protocols ranging from pots and Petri dishes to a hydroponic system. Transgenic hairy roots were obtained by adapting Agrobacterium rhizogenes-based transformation protocols for Dryas species. We compared several DNA extraction protocols for their suitability for subsequent molecular biological analysis. Using CTAB extraction, reproducible PCRs could be performed, but CsCl gradient purification was essential to obtain DNA in sufficient purity for high quality de novo genome sequencing of both Dryas species. Altogether, we established a basic toolkit for the culture, transient transformation and genetic analysis of Dryas sp.